COMPUTATION ANALYSIS OF PARALLEL MATRIX MULTIPLICATION PROGRAM ON LINUX CLUSTER AND KERRIGHED SSI CLUSTER OF HOMOGENOUS AND HETEROGENOUS COMPUTER NETWORK - BERNARD ROGANDA TAMBA (NIM 13204244), HERMOND
In this final project, computer cluster will be built for the purpose of fast computation of parallel matrix multiplication program. Cluster will be constructed under Linux Debian 5.0 operating system on homogenous and heterogenous network of workstations. Parallel execution of matrix multiplication program on the cluster will be made possible by the existence of MPI and OpenMP programming language environment. The implementation based on MPI will use MPICH technology while the technology used for the implementation of OpenMP will be provided by GOMP.